2015
DOI: 10.1021/jf504741t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Six Commercial ELISA Kits for Their Specificity and Sensitivity in Detecting Different Major Peanut Allergens

Abstract: Six commercial peanut enzyme-linked immunosorbent assay kits were assessed for their ability to recover peanut from the standard reference material 2387 peanut butter and also for their specificity in detecting four major peanut allergens, Ara h 1, Ara h 2, Ara h 3, and Ara h 6. The percentage recovery of peanut from peanut butter differed across different kits as well as at different sample concentrations. The highest recovery was observed with the Romer and R-Biopharm kits, while four other kits were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…A similar observation has been reported by Jayasena et al with these two kits with the NIST (National Institute of Standards and Technology, Gaithersburg, MD) standard reference material 2387 peanut butter and is most likely due to the calibration of the kits for which the kit manufacturers supply their own independent standard in absence of international standard materials (Jayasena et al, 2015). The ranges of reactivity of the samples are from 2.8 to 4.5 mg/mL (mean ± SD ¼ 4.0 ± 0.5) for the Neogen kit, and 0.44 to 0.92 (mean ± SD ¼ 0.6 ± 0.1) mg/ml for the Morinaga kit (Table 3).…”
Section: Reactivity In Commercial Kits For Peanut Residue Detection Asupporting
confidence: 79%
See 3 more Smart Citations
“…A similar observation has been reported by Jayasena et al with these two kits with the NIST (National Institute of Standards and Technology, Gaithersburg, MD) standard reference material 2387 peanut butter and is most likely due to the calibration of the kits for which the kit manufacturers supply their own independent standard in absence of international standard materials (Jayasena et al, 2015). The ranges of reactivity of the samples are from 2.8 to 4.5 mg/mL (mean ± SD ¼ 4.0 ± 0.5) for the Neogen kit, and 0.44 to 0.92 (mean ± SD ¼ 0.6 ± 0.1) mg/ml for the Morinaga kit (Table 3).…”
Section: Reactivity In Commercial Kits For Peanut Residue Detection Asupporting
confidence: 79%
“…The ranges of reactivity of the samples are from 2.8 to 4.5 mg/mL (mean ± SD ¼ 4.0 ± 0.5) for the Neogen kit, and 0.44 to 0.92 (mean ± SD ¼ 0.6 ± 0.1) mg/ml for the Morinaga kit (Table 3). Jayasena et al (2015) showed that these two kits have distinctly different specificities for the major allergens. The Neogen kit detects predominantly Ara h 3 with about a 30-fold lower reactivity to Ara h 1, while Ara h 2 and Ara h 6 are minimally recognized.…”
Section: Reactivity In Commercial Kits For Peanut Residue Detection Amentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing ELISA assays available for the detection of peanut proteins it becomes evident that they differ in their ability to recover peanut proteins in terms of their specificity, LOD, and quantification range, as summarized by Jayasena et al [30]. Ara h 2 and Ara h 6 have been shown to be hardly recognized by these assays in contrast to Ara h 3, which was the most recognized allergen.…”
Section: Discussionmentioning
confidence: 99%